2017
DOI: 10.1017/sjp.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Big Five Personality Trait Short Questionnaire: Preliminary Validation with Spanish Adults

Abstract: There are two major advantages of the Big Five Personality Trait Short Questionnaire (BFPTSQ) over other non-commercial short Five-Factor Model personality measures: widen conceptual breadth, and its use in both adolescents and adults. The aim of this study was to explore the psychometric properties of this questionnaire in an adult Spanish sample. Factor, convergent (using the NEO-PI-R), and criterion (using scales that assess happiness and alcohol consumption) validities, internal consistency as well as test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…There are strong reasons to not expect this in our case. First, other measures of the Big Five have shown adequate properties in Spanish samples [43,44]. Second, the previous version of the BFI has also shown that "the Spanish BFI may serve as an efficient, reliable, and factorially valid measure of the Big Five for research on Spanish-speaking individuals" [45].…”
Section: Discussionmentioning
confidence: 99%
“…There are strong reasons to not expect this in our case. First, other measures of the Big Five have shown adequate properties in Spanish samples [43,44]. Second, the previous version of the BFI has also shown that "the Spanish BFI may serve as an efficient, reliable, and factorially valid measure of the Big Five for research on Spanish-speaking individuals" [45].…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the adolescent personality traits (Openness, Extraversion, Agreeableness, Conscientiousness, Emotional Stability) using the Big Five Trait Short Questionnaire (BFPTSQ) ( 66 ). In Northern Ireland we applied the scaled validation by Morizot ( 66 ) and in Colombia we applied the scale validated by Orlet ( 67 ). Self-perceived well-being was assessed using the scale developed by the Children's Society, and based on Huebner's life satisfaction scale ( 37 , 68 ).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The five broad personality traits were measured using the NEO-Five Factor Inventory [39] in Sample 1 and the Big Five Personality Trait Short Questionnaire [40] in Sample 2. The other two scales employed in the present study, the Five Facet Mindfulness Questionnaire-15 [41] that assesses dispositional mindfulness, and the Subjective Happiness Scale [42] that measures happiness, were the same for all the participants.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The BFPTSQ consists of 50 items that assess the FFM broad dimensions on a 5-point response scale (0 = totally disagree, 4 = totally agree): openness, extraversion, agreeableness, conscientiousness and emotional stability. [40] show the reliability and validity results of the Spanish version of the scale. Alpha reliabilities were: openness .83 and .82, extraversion .88 and .86, agreeableness .80 and .70, conscientiousness .86 and .86, and emotional stability .89 and .90 for Sample 2 and Subsample 2A respectively.…”
Section: Neo-five Factor Inventory (Neo-mentioning
confidence: 99%